Cognitive interviewing: a tool for improving questionnaire design / Gordon Willis. - Willis, Gordon B. (Gordon Bruce) (SAGE, 2004)
The design and evaluation of questionnaires and other written and oral materials is a challenging endeavour, fraught with potential pitfalls. This text describes a means of developing survey questions through investigations that probe the thought processes of individuals who are presented with those inquiries.